Minhāj Ta’līm al-Lugah al-‘Arabīyyah Jāmi’ah Dākhilīyyah fī Jāmi’ah al-Sunnah Deli Serdang Indonesia : (Dirāsah Taḥlīlīyyah al-Idāriyyah: al-Takhṭīṭ wa al-Tanfīż) - Amiruddin Siahaan; Muhammad Iqbal; Suriya Jaya; Awaluddin; Rozaanah Rozaanah; Slamet Riyadi; Ade Muhammad Ritonga; Ahmad Zaky (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
This study aims to find out how the Arabic Language Education Curriculum Management at STAI As-Sunnah Deli Serdang is the only strata 1 university in Sumatra that requires all students to apply. This study uses descriptive qualitative research methods. Data were collected by observation, in-depth interviews, and documentation. The findings of this study are a. Arabic Language Education Curriculum Planning; B. Implementation of the Arabic Language Education Curriculum. What this as-sunnah university does can be a model for other universities that have a similar vision, especially in the development of foreign language skills, especially Arabic.